Theology as a Christian Gnosis in the First Three Centuries - René Roux (Wrocławski Przegląd Teologiczny)
During the second and third centuries A.D., challenges from various gnostic groups forced mainstream Christianity to deepen its understanding of its core message. Partially reacting to gnostic teachings, Irenaeus of Lyon, Clement of Alexandria, and Origen all contributed to establishing the methods and contents of the authentic “gnosis,” i.e., the orthodox doctrine of faith, in its relationship to historical knowledge and its moral and spiritual endeavor. The importance given to the regula fidei as criterium veritatis manifests the fundamental desire to be faithful to the original experience of Jesus Christ.